2018
DOI: 10.1016/j.cellsig.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP-induced G protein subunits dissociation monitored in live Dictyostelium cells by BRET reveals two activation rates, a positive effect of caffeine and potential role of microtubules

Abstract: To study the dynamics and mechanisms controlling activation of the heterotrimeric G protein Gα2βγ in Dictyostelium in response to stimulation by the chemoattractant cyclic AMP (cAMP), we monitored the G protein subunit interaction in live cells using bioluminescence resonance energy transfer (BRET). We found that cAMP induces the cAR1-mediated dissociation of the G protein subunits to a similar extent in both undifferentiated and differentiated cells, suggesting that only a small number of cAR1 (as expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…In addition to the observations presented herein, in a previous study, we showed that caffeine also affects the cAR1-mediated heterotrimeric G protein activation, specifically increasing the potency of the cAMP-induced G protein subunit dissociation [47]. We don't think that the effect of caffeine on G protein subunit dissociation plays a role in the other effects of caffeine reported therein, since all the experiments were performed using saturating concentrations of the cAMP stimulus (1 μM) and that, at this concentration, caffeine displays no significant effect on G protein subunit dissociation.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to the observations presented herein, in a previous study, we showed that caffeine also affects the cAR1-mediated heterotrimeric G protein activation, specifically increasing the potency of the cAMP-induced G protein subunit dissociation [47]. We don't think that the effect of caffeine on G protein subunit dissociation plays a role in the other effects of caffeine reported therein, since all the experiments were performed using saturating concentrations of the cAMP stimulus (1 μM) and that, at this concentration, caffeine displays no significant effect on G protein subunit dissociation.…”
Section: Discussionsupporting
confidence: 81%
“…Our work so far has not distinguished between truly different receptors and receptors that are phosphorylated or otherwise modified to change their K D [31,32], which play a role in adaptation to different signal levels in bacteria [33]. If receptor modification is fast compared to the environment's change in concentration c 0 , i.e., can occur before the cell samples a new concentration from P(c 0 ), hedging will be less effective.…”
Section: Discussionmentioning
confidence: 94%
“…During early development of Dictyostelium , secreted cAMP serves as a chemoattractant to organize cells at centers of aggregation ( Meima and Schaap, 1999 ; Jaiswal et al, 2012a ; Jaiswal et al, 2012b ; Fukujin et al, 2016 ; Scavello et al, 2017 ; Singer et al, 2019 ), The receptors for cAMP (CAR1) are surface chemoattractant GPCRs, coupled to Gα2 and Gβγ subunits, which transduce the extracellular signal for directed cell movement ( Janetopoulos et al, 2001 ; Xu et al, 2010 ; Tariqul Islam et al, 2018 ; Adhikari et al, 2021 ). In addition, CAR1 orchestrates a periodic activation/de-activation/re-activation pathway for cAMP generation and clearing, which relays the cAMP signal ( Louis et al, 1993 ; Insall et al, 1994b ; Hereld et al, 1994 ; Thomason et al, 1999 ; McMains et al, 2008 ; Kriebel and Parent, 2009 ; Xu et al, 2010 ; Brzostowski et al, 2013 ; Cao et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many elements of the first phase have been described (see Figure 1 ). Activation of the G protein coupled receptor CAR1 induces the dissociation of the bound Gα2 and βγ subunits ( Janetopoulos et al, 2001 ; Xu et al, 2010 ; Tariqul Islam et al, 2018 ; Adhikari et al, 2021 ). Released βγ subunits stimulate Ras, mTORC2, and other pathways, which are collectively required to activate ACA ( Insall et al, 1994a ; Lee et al, 2005 ; McMains et al, 2008 ; Cai et al, 2010 ; Liao et al, 2010 ; Liao et al, 2013 ; Jaiswal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%